Telaah Pemikiran Abdurrahman Özlem dalam Menentukan Awal Bulan Kamariah: Perspektif Astronomi dan Fikih - Firdiniah, Nur Eka Putri (Azimuth: Journal of Islamic Astronomy, 2024)
This research is motivated by the existing differences in determining the beginning of the lunar month, particularly regarding the timing and location of crescent moon (hilal) observation. The study aims to examine Abdurrahman Özlem’s thoughts on the determination of the beginning of the lunar month and to analyze them from both astronomical and Islamic jurisprudential (fiqh) perspectives. The method used is library research with a descriptive qualitative approach. The primary data consists of Abdurrahman Özlem’s ideas, while secondary data includes books, journals, articles, and other related sources. Data collection was carried out through literature documentation and digital interviews via email. The results of the study show that Abdurrahman Özlem employs the concept of the International Lunar Month Line (ILML) dynamically based on zonal visibility of the crescent moon according to URCUN criteria. In the calculation method (hisab), Özlem uses a minimum elongation criterion of 8° and a minimum altitude of 5°, with the visual observation (rukyat) serving as a verification of the calculation. Astronomically, the ILML divides Earth's regions based on the potential visibility of the crescent moon. From the fiqh perspective, Özlem considers hisab equivalent to rukyat bil ‘ilmi, that is, crescent observation based on scientific calculations. This opinion is supported by several Islamic scholars who allow the use of astronomical calculations in determining the beginning of the lunar month.